Analysis of Mathematics Problem-Solving Ability of Junior High School Students in Emotional Intelligence - Ridina Sekaryanti; Rani Darmayanti; Choirudin Choirudin; Usmiyatun Usmiyatun; Elli Kestoro; Umar Bausir (Jurnal Gantang, 2022)
This study aims to describe the problem-solving skills that students learn from emotional intelligence. This type of research is descriptive and qualitative. The instruments used are questionnaires, tests, and interviews. The questionnaire instrument was used to measure students' emotional intelligence. The test instrument was used to measure problem-solving skills, and interviews were conducted to learn more about problem-solving skills. The subjects of this study were 5 of 15 students from class VIII who were taken as a sample and then given an ability test and analysis based on Krulik and Rudnick's problem-solving steps. Subjects with high emotional intelligence can understand the context of the problem and represent the problem with pictures. Students can link between information, use appropriate strategies or steps, and relevant answers and conclusions. The subject with medium emotional intelligence is rewriting information on the problem using mathematical models and their language. Subjects can relate information, but not all students' answers are correct. Subjects with low emotional intelligence do not make representations or use clear problem-solving strategies. Subjects cannot relate information, so they do wrong calculations and only guess the answer.